2017
DOI: 10.1016/j.drugpo.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Why are some people who have received overdose education and naloxone reticent to call Emergency Medical Services in the event of overdose?

Abstract: Background Overdose Education and Naloxone Distribution (OEND) training for persons who inject drugs (PWID) underlines the importance of summoning emergency medical services (EMS). To encourage PWID to do so, Colorado enacted a Good Samaritan law providing limited immunity from prosecution for possession of a controlled substance and/or drug paraphernalia to the overdose victim and the witnesses who in good faith provide emergency assistance. This paper examines the law’s influence by describing OEND trained P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 79 publications
(109 reference statements)
7
83
0
Order By: Relevance
“…'can I do this?'). Feedback from those involved in other THN programmes has also reported that naloxone was "easy" to administer or that PWID felt "comfortable" when using it (Lankenau et al, 2013;Banjo et al, 2014) often without the need for additional medical support (Koester et al, 2017). In this study, role adequacy varied between individuals and insecurities were evident owing to lack of experience, preparation, and confidence in themselves and in naloxone itself.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…'can I do this?'). Feedback from those involved in other THN programmes has also reported that naloxone was "easy" to administer or that PWID felt "comfortable" when using it (Lankenau et al, 2013;Banjo et al, 2014) often without the need for additional medical support (Koester et al, 2017). In this study, role adequacy varied between individuals and insecurities were evident owing to lack of experience, preparation, and confidence in themselves and in naloxone itself.…”
Section: Discussionmentioning
confidence: 60%
“…These approvals were a source of honour for the individuals involved, reinforcing and strengthening their role as helpers in their communities. Policies such as the 'Good Samaritan Law' in the USA have been created to encourage PWID to call the emergency services without fear of prosecution, yet many still have underlying fear and mistrust of emergency service personnel owing to negative experiences which prevents them from doing so (Koester et al, 2017). Examples of positive…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific challenges include anticipated stigma [89], concerns about moral hazard [90][91][92], or ignorance about state legislation related to naloxone prescribing or dispensing [93,94]. Most states have passed "Good Samaritan laws" to limit criminal liability for bystanders who provide or summon aid when witnessing an overdose incident [95], but the streetlevel effectiveness of such legislation may be limited by anemic implementation and punitive signaling by criminal law and law enforcement, including high-profile "drug-induced homicide" prosecutions, loss of housing, and other legal repercussions [96,97].…”
Section: The Us Opioid Overdose Crisis Response: Multiple Levels Of Pmentioning
confidence: 99%
“…However, challenges remain with giving first responders, including law enforcement, the responsibility of overdose reversal. One significant barrier is that people who use drugs are often hesitant to call emergency services when an overdose occurs due to fear of police involvement [14,15]. First responders also report suffering emotional consequences due to increased numbers of overdose situations [16].…”
mentioning
confidence: 99%